Construction of robustly stable interval polynomial; Mechatronics Engineering and Electrical Engineering: CMEEE 2014, International Conference , Sanya, Hainan, P.R. China, 17-19 October 2014 - Ezangina T. A. Tatiana Aleksandrovna (2014, 2014)
Title screen